Kepuasan Mahasiswa terhadap Layanan Unit Pengelola Program Studi Terkait Pelaksanaan Program MBKM di Universitas Timor - Pius A. L. Berek; Yoseph Nahak Seran; Maria Magd. Namok Nahak; Margareta Diana Pangastuti; Fidelis Atanus (Pusat Riset dan Inovasi Nasional, 2025)
The Independent Learning Campus (MBKM) program is a strategic policy that provides students with opportunities to broaden their knowledge, skills, and experience, both in academic and non-academic fields, through off-campus activities. To support the successful implementation of this program, the Study Program Management Unit (UPPS) plays a crucial role as a provider of academic and administrative services that support students. Therefore, evaluating the level of satisfaction of MBKM participant students with UPPS services is essential for assessing the program's effectiveness, quality, and sustainability. This study aims to measure student satisfaction with UPPS services in the implementation of MBKM by referring to five dimensions of service quality: reliability, responsiveness, capacity, empathy, and infrastructure. The approach used was quantitative with a survey method. Primary data were collected through a Google Form-based questionnaire distributed to MBKM participant students from various study programs at Timor University. Respondents were asked to provide an assessment of each service dimension based on their experience during the program. The results of the descriptive analysis indicate that the level of student satisfaction with UPPS services is very high. More than 90% of students were satisfied with the aspects of reliability, responsiveness, and capacity of the service. The empathy aspect received positive appreciation from 87.9% of students, indicating that the personal interaction and attention provided by UPPS have met the expectations of most participants. However, in terms of facilities and infrastructure, although 84.7% of students expressed satisfaction, 3.3% were dissatisfied, indicating room for improvement in the availability and adequacy of supporting facilities. These findings indicate that in general, UPPS services have met the expectations of MBKM student participants.